2019
DOI: 10.18203/2394-6040.ijcmph20193471
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and its coping strategies among the police personnel of the Chitradurga city: a cross-sectional study

Abstract: Background: Everyone relishes having a peaceful and safe society to live in. But nobody thinks about the police who work hard to keep our community safe and secure. They have to face potentially hazardous situations that can result in physical or mental trauma or even death in the line of duty. This study will help to reveal the stress and coping strategies employed by the police personnel of Chitradurga city. To determine the stressful situations faced by the police personnel and to ascertain the positive &am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Another study by Furmeen and Reddy (2019) Meanwhile, Jonyo (2015) discovered that police officers are exposed to high levels of occupational stress and are rated as having average job performance. In addition, the research demonstrated that occupational stress negatively impacts the job performance of police officers.…”
Section: Foreign Literaturementioning
confidence: 99%
“…Another study by Furmeen and Reddy (2019) Meanwhile, Jonyo (2015) discovered that police officers are exposed to high levels of occupational stress and are rated as having average job performance. In addition, the research demonstrated that occupational stress negatively impacts the job performance of police officers.…”
Section: Foreign Literaturementioning
confidence: 99%